Antibiotic prophylaxis in low risk patients undergoing laparoscopic cholecystectomy - Kumar, S; Lakhey, PJ; Vaidya, P; Patowary, BN; Praveen, CR; Shrestha, P (Journal of College of Medical Sciences-Nepal, 2012)
Laparoscopic cholecystectomy is the 'gold standard' for benign diseases of gallbladder. It has rapidly gained popularity and it is one of the commonly performed operations in Nepal. The need for antibiotic prophylaxis when performing an elective laparoscopic cholecystectomy may not be as important as it is thought in low risk group. Despite, low postoperative infection rate in laparoscopic cholecystectomy in low risk group, the same criteria of antibiotic prophylaxis previously applied to conventional surgery are routinely used for laparoscopic surgery, even though its actual need has not been ascertained. Aim of this study was to assess the efficacy of antibiotic prophylaxis in elective laparoscopic cholecystectomy with respect to postoperative Surgical Site Infection (SSI) in low risk group. Study was carried out in The Department of Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal from May 2005 to June 2006 (14 months).This was a prospective randomized study done on 104 consecutive patients undergoing laparoscopic cholecystectomy. Patients were randomized into case group (group A) and control group (group B) with 52 patients in each group. Two and four patients from Group A and Group B respectively were excluded. In Group A, 50 patients received one gram ceftriaxone intravenously 30 minutes prior to induction of anesthesia and in Group B, all 48 patients received 10 milliliters (ml) of isotonic sodium chloride solution intravenously 30 minutes before induction. In both groups, age, sex, ultrasonogram findings, duration of surgery, American society of anesthesiologists patient classification score, antibiotic administration, bile spillage during surgery, length of postoperative hospital stay and postoperative SSI were recorded. Patients were advised to follow up in Surgical Out-patient Clinic if there was any evidence of SSI within 30 days. SSI was reported and classified as, superficial incisional, deep incisional or space / organ SSI. There were a total of 98 patients included in the study; 50 in Group A and 48 in Group B. In group A, three (6%) patients and in Group B, also three (6.3%) patients had superficial incisional SSI. None of them had deep or organ / space SSI. Comparison of data showed no statistically significant difference between two groups (P- 1.00). DOI: http://dx.doi.org/10.3126/jcmsn.v7i1.5962 JCMSN 2011; 7(1): 12-18